Bone Mineral Density after Weight Gain in 160 Patients with Anorexia Nervosa - Achamrah, Najate; Coëffier, Moïse; Jésus, Pierre; Charles, Jocelyne; Rimbert, Agnès; Déchelotte, Pierre; Grigioni, Sébastien (Frontiers in Nutrition, 2017)
Low bone mineral density (BMD) is a frequent complication in anorexia nervosa (AN). There are controversial points of views regarding the restoration of bone mineralization after recovery in AN. We aimed to assess changes of BMD at 3 years in patients with AN, and to explore the relationships between body composition, physical activity and BMD. Patients with AN were included from 2009 to 2011 in a first visit (T0) with evaluation of weight, height, Body Mass Index (BMI), body composition (FM: Fat Mass and FFM: Fat Free Mass), and BMD. Those who had low BMD, either osteoporosis or osteopenia, were admitted in a second visit (T1) to carry out a new bone densitometry examination and body composition; they were also asked for their physical activity. At T0, our study involved 160 patients. Low BMD was observed in 53.6% of them and significant factors associated to demineralization were lower BMIs and higher duration of AN. At 3 years follow-up (T1), 42 patients were involved and no significant changes in BMD were observed despite body weight increase (3.8±6.1 kg). Interestingly, FM gain was a significant factor associated to BMD improvement at follow-up. Our findings suggest that the restoration of normal bone values is not related to the increase of body weight, at least after 3 years.